Borexino and Geo-Neutrinos: Unlocking the Earth's Secrets. (2nd July 2016) - Meroni, E.; Zavatarelli, S.
Abstract : Neutrinos and their matter counterpart—antineutrinos—are helping scientists to address a varied range of applications beyond fundamental particle physics: in particular they are presently offering a unique possibility to established independently the absolute amount of U and Th in the Earth's crust and mantle, thus settling a very long discussion about the Earth's internal heat sources initiated almost 200 years ago.